1976
DOI: 10.1063/1.88892
|View full text |Cite
|
Sign up to set email alerts
|

Efficient high-power operation of the cw far-infrared waveguide laser

Abstract: Order-of-magnitude increases in output power and efficiency have been obtained from optically pumped FIR lasers using a new FIR waveguide laser geometry and a new output coupler. Conversion efficiencies 5–15% of the theoretical maximum are reported for several lines between 71 and 1222 μm and cw output of 400 mW at 118 μm and 40 mW at 496 μm are obtained from a laser 2 m in length. These results indicate that the stronger FIR transitions are capable of cw operation at the 0.1–1.0-W level for 100 W of CO2 pump … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…The results are in Fig. 5 The THz energy vs. the CH 3 OH pressure for 9P (16). a good agreement with the pressure [19,20].…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…The results are in Fig. 5 The THz energy vs. the CH 3 OH pressure for 9P (16). a good agreement with the pressure [19,20].…”
Section: Introductionsupporting
confidence: 71%
“…Just at that time, methanol has become the THz laser-active molecule with the richest spectral lines. More than 570 lines from 19 to 3030 μm have been observed for the parent l2 CH 3 16 OH species alone and about 2000 Lines in total for all of the isotopomers of methanol [2][3][4][5]. In the past few years, most research has been dedicated on the assignments of the observed THz laser lines from methanol and its isotopomers pumped by CW CO 2 lasers or chopped CO 2 lasers [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…of the cavity (same hole in the center of the two mirrors), it is expected that the same power is generated from the pump side (but not measured), and consequently, the total generated power should be 20 µW, corresponding to an optical conversion efficiency of 7.7 × 10 −4 (differential efficiency of 0.82 mW/W). For OPTL, the theoretical limit for the optical conversion efficiency, 17 assuming a rapid vibrational relaxation, a lossless cavity, and an ideally coupled laser is given by η opt = 1 /2(ν THz /ν pump ) = 1.8 × 10 −2 . The measured efficiency is 4.3% of the theoretical maximum.…”
Section: -2mentioning
confidence: 99%
“…2 The probing laser beams are produced by two optically pumped CH 3 OH lasers from the MIRI system for TFTR in PPPL. 3 The cavities of these lasers consist of a copper mirror with a 6 mm diameter hole in the center for the input of CO 2 pump beam, and a giant hole output coupler 4 with a coupling hole of 11 mm in diameter. To be able to design the optics with confidence, the propagation characteristics of the laser beams in the far field are measured in detail.…”
Section: A Laser Systemmentioning
confidence: 99%